Digital presence in Instagram: study of a brand of slow fashion - Nogueira de Moraes, Priscila (2024)
Instagram is a social network that is on the rise and has been widely used by people and brands. In this medium, the image is the main message, as it is the focus of interactions. The way brands position themselves on Instagram corresponds to their digital presence, which often influences their relationship with the public. That said, this work aimed to investigate the digital presence and its phases of the clothing brand 787 Shirts on Instagram. Thus, the specific objectives were: to identify the predominant digital presence phase for the selected brand; verify characteristics of formats and language of publications; verify that content predominates in brand publications. The research was qualitative, with descriptive analysis from a total of 13 publications of the fashion brand named 787 Shirts. The results demonstrate that the brand invests more in the relationship phase of the digital presence, through publications with images of the products used by models and collaborators of various styles and mannequins. In conclusion, this generates interactions of its customers and followers, through the identification of consumers and also with conscious consumption.